Pseudowintera colorata (Raoul) Dandy Hydro-Alcohol Leaf Extract Inhibits Bacterial Triggers of Some Autoimmune Inflammatory Diseases - Barillot, Celia; Davis, Craig; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Pseudowintera colorata (Raoul) Dandy is an evergreen shrub which is endemic to New Zealand. Decoctions, infusions and essential oils produced from the leaves were used traditionally to treat a variety of bacte- rial diseases. Despite this, P. colorata leaf extracts have not been rigorously examined for inhibitory activity against bacterial triggers of autoimmune inflammatory diseases. Methods: A P. colorata hydro-alcohol leaf extract was analysed for antioxidant capacity by the DPPH free radical scavenging assay. Growth inhibitory activities against bacterial species associated with initiating rheumatoid arthritis, ankylosing spondylitis, multiple sclerosis and rheumatic fever were determined by disc diffusion assay and quantified by MIC determination. Toxicity was determined by Artemia franciscana bio- assay. Results: The P. colorata hydro-alcohol leaf extract displayed good DPPH radical scavenging activity, with an antioxidant capacity of 52 µg/ mL ascorbic acid equivalency. The extract inhibited the growth of all of the bacterial triggers of autoimmune inflammatory diseases tested. It was a particularly potent inhibitor of A. baylyi, with MIC values as low as 427 µg/ mL against the clinical strain. P. mirabilis and P. vulgaris were also highly susceptible to the P. colorata hydro-alcohol leaf extract, with MIC values of approximately 800-900 µg/mL against all strains. The extract was also a moderate growth inhibitor (MIC >1000 µg/mL) of all other bacterial strains tested. The extract was determined to be nontoxic in the Artemia francis- cana nauplii bioassay with 24 h LC50 values substantially >1000 µg/mL, indicating its safety for therapeutic use. Conclusion: The lack of toxicity of the P. colorata leaf extracts and their growth inhibitory bioactivity against a panel of bacterial triggers of autoimmune inflammatory diseases indicate their potential in the prevention and treatment of these diseases in geneti- cally susceptible individuals.
Keywords: Winteraceae; Horopito; Pepperwood; Autoimmune Inflamma- tory Disease; Rheumatoid Arthritis; Ankylosing Spondylitis.